lstithmār al-Amwāl fī al-Fiqh al-lslāmīy - Surahman Hidayat Aziz. (Al-Jami'ah: Journal of Islamic Studies, 2001)
Islam encourages Muslims to invest their money and goods in order that their economic and social conditions can be improved. Investment is actually basic needs for human beings. It is also social needs for community. According to Islamic teaching, investrnent is part of obligation for Muslims. This article tries to explore how importance investrnent is according to Islamic Law. It describes that Islam encourages Muslims to invest their money and goods. The writer states that according to Islam,Wealth should be developed. He also describes various kinds of investment implemented by Islamic Bank that have big impact on individual and communal economy. According to Islam, investment is part of human obligation as a representative of God on earth (khalifatullah fi al-ardl). There are three important point described by the writer, namely, 1.Using wealth for beneficial matters. 2. Investing wealth for preserving and developing it so that it is useful for it owner and community.3. Transferring ownership to others voluntarily. Furthermore, the writer also describes the characteristics of Islamic investment namely, 1. Differentiating between good and forbidden. 2. Not implementing interest. Considering community needs according to Islamic priority. 4. Valuing works. 5. Trying to get benefit fairly. 6. Investment can be renewed and developed.